Design, synthesis, and biological activity of novel tetrahydropyrazolopyridone derivatives as FXa inhibitors with potent anticoagulant activity. Issue 10 (15th May 2017) - Sun, Xiaoqing; Hong, Zexin; Liu, Moyi; Guo, Su; Yang, Di; Wang, Yong; Lan, Tian; Gao, Linyu; Qi, Hongxia; Gong, Ping; Liu, Yajing
Graphical abstract: Highlights: A series of compounds was synthesized and evaluated for anticoagulant activity. Enzymatic assay and venous thrombosis test in vivo analysis of potent compounds. Most promising15c showed an IC50 value of 0.14 μM and 98% inhibition rate in vivo. Abstract: A series of novel tetrahydropyrazolopyridone derivatives containing 1, 3, 4-triazole, triazolylmethyl, and partially saturated heterocyclic moieties as P2 binding element was designed, synthesized, and evaluated in vitro for anticoagulant activity in human and rabbit plasma. All compounds showed moderate to significant potency, and compounds15b, 15c, 20b, 20c, and22b were further examined for their inhibitory activity against human FXa in vitro. While compounds15c and22b were tested for rat venous thrombosis in vivo. The most promising compound15c, with an IC50 (FXa) value of 0.14 μM and 98% inhibition rate, warranted further investigation as an FXa inhibitor.